Comparison of different DNA isolation methods and use of dodecyle trimethyl ammonium bromide (DTAB) for the isolation of DNA from meat products (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The identification of meat species in meat products is important for protection of human health, economic reasons, religious factors and for controlling the compliance with food regulations. For this purpose, DNA must be obtained in good quality and quantity. The aim of this study was to compare different DNA isolation methods from different meat products.Materials and methods: Comparison among different DNA isolation methods was done. DNA was isolated from different meat products (e.g., sucuk, salami, sausage, braised meet, meatball and pastrami). The methods included phenol/chloroform, DNA isolation kit, Cetyl Trimethyl Ammonium Bromide (CTAB) and Dodecyle Trimethyl Ammonium Bromide (DTAB).Results: Although DNA was obtained from all of these methods, the phenol/chloroform and DNA isolation kit methods were found to be the most effective methods for obtaining high quantity DNA. RNA contamination was determined to be common in DTAB method. High quantity of DNA and RNA contamination in terms of quality was detected in CTAB method. Ruminant specific 16S rRNA primer was used to amplify genomic DNA by polymerase chain reaction and all samples were amplified except for some samples of DTAB.Conclusion: DNA isolation kit, another best method, is recommended due to quality and quantity of DNA for researchers who do not want that phenol/chloroform method have toxic substances. This study is also the first study in which DTAB method is used for DNA extraction from meat products.http://doi.org/10.5455/javar.2016.c175